Transcranial direct current stimulation for acute major depressive episodes: Meta-analysis of individual patient data. (June 2016) - Brunoni, André R.; Moffa, Adriano H.; Fregni, Felipe; Palm, Ulrich; Padberg, Frank; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Bennabi, Djamila; Haffen, Emmanuel; Alonzo, Angelo; Loo, Colleen K.
Abstract : Background: Transcranial direct current stimulation (tDCS) is a non-pharmacological intervention for depression. It has mixed results, possibly caused by study heterogeneity. Aims: To assess tDCS efficacy and to explore individual response predictors. Method: Systematic review and individual patient data meta-analysis. Results: Data were gathered from six randomised sham-controlled trials, enrolling 289 patients. Active tDCS was significantly superior to sham for response (34% v. 19% respectively, odds ratio (OR) = 2.44, 95% CI 1.38–4.32, number needed to treat (NNT) = 7), remission (23.1% v. 12.7% respectively, OR = 2.38, 95% CI 1.22–4.64, NNT = 9) and depression improvement ( B coefficient 0.35, 95% CI 0.12–0.57). Mixed-effects models showed that, after adjustment for other predictors and confounders, treatment-resistant depression and higher tDCS 'doses' were, respectively, negatively and positively associated with tDCS efficacy. Conclusions: The effect size of tDCS treatment was comparable with those reported for repetitive transcranial magnetic stimulation and antidepressant drug treatment in primary care. The most important parameters for optimisation in future trials are depression refractoriness and tDCS dose.